Amantadine resistance among hemagglutinin subtype 5 strains of avian influenza virus - Wainright, P O; Perdue, M L; Brugh, M; Beard, C W (Avian diseases, 1991)
Several avian influenza virus strains of hemagglutinin subtype 5 were assayed for sensitivity to the antiviral drug amantadine. Most strains exhibited little sensitivity to the drug as measured by plaque reduction. The A/Chicken/Scotland/59 (CS59), however, was highly sensitive, making it easily distinguishable from the other H5 strains. Drug sensitivity of the viruses was also assayed in chicken embryos. The in ovo patterns of amantadine sensitivity differed from those detected in cell culture. The CS59 isolate could not be distinguished from all the other strains on the basis of its response to amantadine in ovo. Although amantadine protected chickens inoculated with CS59 from morbidity and mortality, drug-resistant viruses were readily isolated from the infected birds. As found with other amantadine-resistant variants, the structure of the matrix gene was altered in the resistant isolates. These results demonstrate that amantadine resistance is widespread among avian influenza viruses of the H5 subtype, that drug sensitivity in cell culture does not necessarily reflect responses to amantadine in ovo and in vivo, and, as previously found, amantadine-resistant derivatives of H5 strains may be isolated from birds protected by the drug.